Evaluation of Healthcare Service Digitalization Using the HOT-Fit Method - Ekananda, Ferio Pristiawan (Journal La Sociale, 2025)
Digital transformation in the healthcare sector has become a crucial element in enhancing the quality, efficiency, and transparency of public services. This study aims to evaluate the success of healthcare service digitalization at RSUD dr. Hasri Ainun Habibie Gorontalo using the HOT-Fit (Human, Organization, Technology, and Net Benefit) framework. The research employed a quantitative approach with survey instruments administered to 104 respondents, consisting of both medical and non-medical staff. The findings indicate that all HOT-Fit indicators fall within the "very high" category, particularly information quality (3.47) and user satisfaction (3.38), both of which show a strong correlation with the net benefits of digitalization. The main challenges identified include unstable internet connectivity and application fragmentation, although most users perceive the system as functioning effectively. Recommendations derived from this study include improving network infrastructure, developing integrated digital platforms (super apps), and providing advanced technical training for human resources. These results reinforce the significance of integrating human, organizational, and technological aspects to ensure the success of digital transformation in regional healthcare services.